PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN BAGIAN PERGUDANGAN PADA PT. BUKIT ASAM ( PERSERO) TBK TANJUNG ENIM - Darwin Kesuma (Fakultas Ekonomi Universitas Tridinanti Palembang, 2017)
The purpose of this studyis to see the effect ofcompensation to employee performance at Warehouseof PT. Bukit Asam (Persero) Tbk Tanjung Enim. The population in this study are 43 employees of Warehouseof PT. Bukit Asam (Persero) Tbk Tanjung Enim. The result of this study obtained a regression formulaY = 23.996 + 0.467X + e. That means that if incentives (X) increased 0,467 points then theemployees performance (Y)will increase by 0,467 points. The results of the analysis obtained correlation coefficient r = 0.600. This means incentives (X) have positive influence toemployees performance (Y) of Warehouse of PT. Bukit Asam (Persero) Tbk Tanjung Enim.Determinant coefficient has 0.36 point or 36%. It means that incentives (X) give 36% contribute to employees performance (Y). The remaining 64% are influenced by other factors not examined by the author. Hypothesis t-test obtained t-value = 4.802 higher than t-table = 2, 020 which means that thereis a significant difference between the incentive to Warehousing Part employee performance at PT. Bukit Asam (Persero) Tbk Tanjung Enim. Keywords: Compensation, Performance